2011
DOI: 10.1111/j.1365-3156.2010.02717.x
|View full text |Cite
|
Sign up to set email alerts
|

Can piperonyl butoxide enhance the efficacy of pyrethroids against pyrethroid‐resistant Aedes aegypti?

Abstract: Summarybackground Pyrethroid resistance can be considered the main threat to the continued control of many mosquito vectors of disease. Piperonyl butoxide (PBO) has been used as a synergist to help increase the efficacy of certain insecticides. This enhancement stems from its ability to inhibit two major metabolic enzyme systems, P450s and non-specific esterases, and to enhance cuticular penetration of the insecticide.objective To compare the mortality of a characterized resistant Aedes aegypti strain, Nha Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 33 publications
1
104
2
Order By: Relevance
“…A study in Vietnam reported that pyrethroid resistance in Ae. aegypti was conferred by V1016I mutations and cytochrome P450s; adding PBO enhanced the efficacy of pyrethroids (Bingham et al, 2011). In Malaysia, although kdr mutations (V1016G and F1534C) were present in Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Vietnam reported that pyrethroid resistance in Ae. aegypti was conferred by V1016I mutations and cytochrome P450s; adding PBO enhanced the efficacy of pyrethroids (Bingham et al, 2011). In Malaysia, although kdr mutations (V1016G and F1534C) were present in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, F1534C and V1016I, a valine to isoleucine transversion in domain II, are prevalent (Saavedra- Rodriguez et al, 2007;Harris et al, 2010). The V1016I mutation has also been reported from Vietnam, but has not been detected in Thailand (Bingham et al, 2011). Interestingly, the V1016G mutation is often found with a serine to proline mutation (S989P) in domain II (Stenhouse et al, 2013;Kawada et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of a Synergistic effect of Piperonyl Butoxide (PBO) on roof and side panels of LLINs have improved the efficacy of LLINs against resistant mosquitoes [19][20][21][22]. It has a potency of increasing cuticular penetration of insecticides and increase mosquito susceptibility [23].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, LLINs have an improved synergistic effect of PBO on top or on top and all side panels for managemenet of insecticide resistance [20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Modulators such as piperonyl butoxide (PBO) and menadione (MEN) are very useful to understand how biotransformation affects the toxicity of a chemical under investigation (20,21). PBO (IUPAC name: 5-[2-(2-butoxyethoxy) ethoxymethyl]-6-propyl-1,3-benzodioxole; CAS no: 51-03-6) is a methylenedioxyphenyl compound used to enhance the potency of certain pesticides by inhibiting CYP450s and esterases (22)(23)(24). As Tomizawa and Casida (5) stated in their review that PBO synergized with IMI in toxicity to insects, we wondered what would be the toxicity (oxidative stress and cholinesterase activity) of this combination in mammals.…”
mentioning
confidence: 99%